Financial Market Efficiency: Analysis of bond and derivatives market - Lee, Joon Won (2005)
1 In the economy, efficiency is essential for the wealth of nations, firms, and individuals. The role of financial market is getting more and more crucial in the modern economy. Consequently, efficiency of the financial market has become one of the core factors in the conomic development. The modern financial market system has rapidly developed in a very short time period. Like a growing business, the financial market has been attempting to put its numerous fascinating ideas and theories into practice for a single aim Ã¢ÂÂ wealth creation or maximization of scarce capital resources. Having had the common denominator of wealth creation or maximization, the financial market has had troubles in achieving the goal in an efficient way. If the financial market did not perform efficiently, it could lead into a lower economic activity and productivity as a result of the failure of the best use of scarce capital resources. Based on the debt and derivatives markets, this paper will examine how efficiently the two financial markets are functioning and contributing to the maximization of market participants' wealth or utilities. Considering the fact that accurate estimation and calculation of the risks and returns are the key factors in investment, there will be a discussion on how financial instruments in the debt and derivatives market are structured and priced from a fair valuation perspective. Interest rate risk will be the main topic in the debt market along with how credit risk is managed in the derivatives market.